2019
DOI: 10.1101/836585
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

WAVE complex self-organization templates lamellipodial formation

Abstract: How local interactions of actin regulators yield large-scale organization of cell shape and movement is not well understood. For example, why does the WAVE complex build lamellipodia, the broad sheet-like protrusions that power cell migration, whereas the homologous actin regulator N-WASP forms spiky finger-like actin networks? N-WASP is known to oligomerize into focal condensates that generate an actin finger. In contrast, the WAVE complex exhibits the linear distribution needed to generate an actin sheet. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 90 publications
2
8
0
Order By: Relevance
“…It also highlights the possibility of unprecedented cargo selectivity functions for the CG pathway in a manner similar to that described for numerous other endocytosed proteins following different endocytosis routes. Moreover, our findings explain the previously reported link between the CG pathway components, IRSp53 and Arf1, and adhesion phenotypes: IRSp53 contributes to cell migration and invasion through multiple mechanisms, including filopodia generation 31,32 , and curvature sensing with WAVE at the neck of membrane invaginations 33 . Arf1 depletion results in defective adhesion and migration in MDA-MB-231 cells 34-36 , and our finding of Arf1 involvement in integrin endocytosis sheds light on the mechanism behind these observations.…”
Section: Discussionsupporting
confidence: 84%
“…It also highlights the possibility of unprecedented cargo selectivity functions for the CG pathway in a manner similar to that described for numerous other endocytosed proteins following different endocytosis routes. Moreover, our findings explain the previously reported link between the CG pathway components, IRSp53 and Arf1, and adhesion phenotypes: IRSp53 contributes to cell migration and invasion through multiple mechanisms, including filopodia generation 31,32 , and curvature sensing with WAVE at the neck of membrane invaginations 33 . Arf1 depletion results in defective adhesion and migration in MDA-MB-231 cells 34-36 , and our finding of Arf1 involvement in integrin endocytosis sheds light on the mechanism behind these observations.…”
Section: Discussionsupporting
confidence: 84%
“…The resulting structure shows minimal steric clashes between each Scar/WAVE complex suggesting that this dimerization may be a conserved feature of DUF1394 containing proteins. In line with this observation, it has been reported that the Scar/WAVE complex can form higher-order oligomers ( Pipathsouk et al., 2019 ).…”
Section: Resultssupporting
confidence: 68%
“…Indeed, if autoinhibitory dimers are a conserved feature of DUF1394 domains, the possibility that Scar/WAVE could also form autoinhibited dimers and that CYRI could disrupt such interactions cannot be excluded. In fact, there have been several reports suggesting that the Scar/WAVE complex could form oligomeric structures ( Pipathsouk et al., 2019 ), making this an attractive question for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…2G). Finally, since WAVE complex exhibits a preference for saddle curvatures (Pipathsouk et al, 2019), we measured its enrichment to bead-induced invaginations. While WAVE complex transiently enriched to some beads, it failed to persistently enrich (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that WASP is both curvature-sensitive and essential for HL-60 alignment to nanoridges supports WASP-mediated actin polymerization as a mechanism by which loosely adherent cells can sense and align with their substrate's topology. Membrane curvature has emerged as a key regulator for WASP family proteins; other NPFs from this family such as N-WASP and WAVE also preferentially enrich to sites of membrane curvature (Lou et al, 2019;Pipathsouk et al, 2019). Unique curvature preferences among WASP family NPFs could help differentiate their organization and inform the morphology of the actin networks they generate.…”
Section: Discussionmentioning
confidence: 99%